Inhibition of Indoleamine 2, 3 Dioxygenase Does Not Improve Cancer-Related Symptoms in a Murine Model of Human Papilloma Virus–Related Head and Neck Cancer. (August 2019) - Vichaya, Elisabeth G; Vermeer, Daniel W; Budac, David; Lee, Anna; Grossberg, Aaron; Vermeer, Paola D; Lee, John H; Dantzer, Robert
The expression of indoleamine 2, 3 dioxygenase (IDO) by tumors can contribute to immunotolerance, and IDO induced by inflammation can also increase risk for the development of behavioral alterations. Thus, this study was initiated to determine whether IDO inhibition, intended to facilitate tumor clearance in response to treatment, attenuates behavioral alterations associated with tumor growth and treatment. We used a murine model of human papilloma virus–related head and neck cancer. We confirmed that tumor cells express IDO and expression was increased by radiotherapy. Interestingly, inhibition of IDO activation by the competitive inhibitor 1-methyl tryptophan mildly exacerbated treatment-associated burrowing deficits (burrowing is a sensitive index of sickness in tumor-bearing mice). Genetic deletion of IDO worsened tumor outcomes and had no effect on the behavioral response as by decreased burrowing or reduced voluntary wheel running. In contrast, oral administration of a specific inhibitor of IDO1 provided no apparent benefit on the tumor response to cancer therapy, yet decreased voluntary wheel-running activity independent of treatment. These results indicate that, independent of its potential effect on tumor clearance, inhibition of IDO does not improve cancer-related symptoms.